Complexity of Stakeholder Interaction in Applied Research - Ntshinga, Wonga (My University, 2013)
Applied research in complex integrated settings should be recognized as an endeavour that requires transdisciplinary and multi-sectorial stakeholder interactions. The problems faced in society are quite complex, requiring participation and knowledge from diverse aspects of society, including different disciplines (academia), communities, civil society, and government. Successful applied research relies on nurturing these key stakeholder relationships and interactions. This paper explores the key challenges of stakeholder interaction in applied research in three disciplines in the South African context, based on literature and the experience of authors in their disciplines. The three disciplines include information and communication technology for development, town and regional planning, and natural resource management. We attempt to also compare and contrast these challenges across the disciplines, to identify any commonalities and differences. After considering the mutual challenges and adaptive solutions to address these challenges in the different disciplines, we identify that all three areas in relation to stakeholder interaction appear to exhibit characteristics of complex systems, hence motivating to view applied research as a complex system. In this sense, complexity theory may provide a common language between the different disciplines examining trans-disciplinary stakeholder interaction in applied research from a shared perspective
Keywords: Applied Research; Research; Complexity Theory; Town Planning; Information and Communication Technology; Resource Management